The Association Between Wait Times and Patient Satisfaction: Findings From Primary Health Centers in the Kingdom of Saudi Arabia. (8th July 2019) - Alrasheedi, Khaled Falah; AL-Mohaithef, Mohammed; Edrees, Hanan H.; Chandramohan, Sriram
Background: It is no doubt that longer wait times can affect patient care and patients' willingness to seek health-care services. Not only does this disrupt the continuity of treatment and care, but it also negatively impacts patient outcomes. During the past few years, the concept of patient satisfaction has become a vital component in assessing the delivery and efficiency of care. Patient satisfaction is a performance indicator that measures the extent to which patient is content and satisfied with the level of care provided by health-care institutions and providers. Therefore, this research examined association between the wait times and patient satisfaction in selected primary health-care centers in Al Qassim region in the Kingdom of Saudi Arabia. Methodology: A patient satisfaction questionnaire was administered to 850 patients, which collected patient perceptions on the delivery of care at health-care centers in Al Qassim City. Outcome measures included wait times for: registration and payment, seeing the physician, performing radiation and assays, and dispensing the medications. Results: The response rate was 72.94% (n = 620). The study found that 27.90% of the participants stated that the wait time to see the physician ranged between 21 and 30 minutes. Overall patients were mainly dissatisfied for wait times in relation to medication dispensation, vital signs measurement, dental consultations, and radiological investigation. The study found a positive association between the patient satisfaction and their education, marital status, and job. A significant regression equation was established between the patient satisfaction and age-group and literacy. Conclusion: The study advocated the need for recent technology, sufficient staffing, and patient-centered friendly methods to reduce wait times.